The impact of catholic titles on the perception and aestheticisation of violence in figurative painting - Campbell-de la Cruz, Atenas; Duran Barraza, Gabriela (2024)
The impact of Catholic Titles on figurative paintings depicting violence were studied using both explicit and implicit measures. When paintings were described as Catholic, they were significantly rated as more beautiful and interesting, and less violent than when they were described as Non-Catholic. Therefore, demonstrating that Catholic themes associated with these artworks overshadow their violent content. This was demonstrated via hedonic ratings. Thus, suggesting an aestheticisation of violent imagery when connected to Catholic themes. Implicit responses, assessed using the Implicit Association Test, showed faster responses when Violent Catholic Paintings were associated Positive Adjectives and slower responses were associated when violent Non-Catholic Paintings were associated with Negative Adjectives. These implicit responses confirm previous explicit results.